Bibliotherapy: Use and Characterization in Pediatric Hospital Contexts in Santiago, Chile - Rioseco Vergara, María Paz; Flores Fernández, Cherie (Revista General de Información y Documentación, 2021)
The present research aims to identify and characterize the application of bibliotherapy in a pediatric hospital context in Santiago de Chile. For this, a qualitative methodology was used, conducting semi-structured interviews with seven representatives of organizations linked to the investigated hospitals. The content analysis carried out resulted in the creation of four categories – background and organization; characteristics of activities related to books, reading and bibliotherapy; methodology of activities related to books, reading and bibliotherapy; perception about bibliotherapy. It was possible to characterize the activities carried out in the hospital centers with these categories. Among the most relevant findings, it was found that there is no formal use of bibliotherapy as therapeutic or recreational within the investigated hospitals, but rather, a use of reading and books for mostly recreational purposes.
Keywords: Bibliotherapy; Children; Pediatric Hospitals; Library Science.